1999
DOI: 10.1161/01.hyp.33.2.658
|View full text |Cite
|
Sign up to set email alerts
|

Low Calorie Diet Enhances Renal, Hemodynamic, and Humoral Effects of Exogenous Atrial Natriuretic Peptide in Obese Hypertensives

Abstract: The expression of the natriuretic peptide clearance receptor is abundant in human and rat adipose tissue, where it is specifically inhibited by fasting. In obese hypertensives, plasma atrial natriuretic peptide (ANP) levels were found to be lower than in obese normotensives. Therefore, the increased adipose mass might influence ANP levels and/or its biological activity. The aim of the present study was to evaluate whether the humoral, hemodynamic, and renal effects of exogenous ANP in obese hypertensives might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 31 publications
5
31
0
6
Order By: Relevance
“…It has recently been shown that short-term caloric restriction enhances ANP-induced diuresis and decreases arterial blood pressure. 14 Previous studies in animals help to interpret these findings and our results. Rat and human adipose tissue contain high levels of NPr mesenger RNA 37,38 and large numbers of clearance receptor binding sites (NPr-C).…”
Section: International Journal Of Obesitysupporting
confidence: 66%
“…It has recently been shown that short-term caloric restriction enhances ANP-induced diuresis and decreases arterial blood pressure. 14 Previous studies in animals help to interpret these findings and our results. Rat and human adipose tissue contain high levels of NPr mesenger RNA 37,38 and large numbers of clearance receptor binding sites (NPr-C).…”
Section: International Journal Of Obesitysupporting
confidence: 66%
“…4,15 Relative wall thickness (RWT) was calculated as 2ϫ end-diastolic PWT/LV internal dimension. 2,25 Increased RWT was present when this ratio exceeded 0.43, which represents the 97.5th percentile in previously described normal subjects. 26 Normal geometry was present when LV mass/BSA and RWT were normal, whereas normal LV mass/BSA and increased RWT was classified as concentric remodeling.…”
Section: Echocardiographymentioning
confidence: 56%
“…Third, the response to exogenous natriuretic peptide therapy for congestive heart failure may be modified in the setting of obesity, in part because of increased peripheral clearance of these molecules. 32 Lastly, our findings raise the possibility that augmentation of the natriuretic peptide system may reduce the susceptibility of obese individuals to hypertension. Although the role of pharmacological manipulation of the natriuretic peptide axis remains to be defined, it is possible that weight loss could enhance endogenous natriuretic peptide activity in such individuals.…”
Section: Discussionmentioning
confidence: 75%